Health-promoting behaviors and menopausal symptoms: An interventional study in rural India - Ekta Malik; Poonam Sheoran; Adiba Siddiqui (Wolters Kluwer Medknow Publications, 2018)
Background: Menopausal transition initiates with menstrual cycle length variety and finishes when last menstrual period happens. As life expectancy has increased, a menopausal woman has to spend one-third of her life span with estrogen deprivation stage that leads to major long-term symptomatic and metabolic complications. Methods: This was a quasi-experimental study conducted on 103 menopausal women between 40 and 60 years of age residing in Ambala district, Haryana. In the experimental group, women received lifestyle modification program that includes six domains, i.e., health responsibility, physical activity, nutrition, spiritual growth, interpersonal relations, and stress management. Intervention was divided into two sessions of total 2-h duration on 2 consecutive days. Sociodemographic pro forma, Menopausal Rating Scale, and Health Promoting Lifestyle Profile II were used to collect data from women through face-to-face interview. Results: There was a significant difference (P < 0.05) in mean menopausal symptom score and mean health-promoting behavior score in the experimental group after the intervention, but there was no significant difference in the comparison group (P > 0.05). It was revealed that there was no significant difference between the groups with regard to mean menopausal symptom score and mean health-promoting behavior score before intervention (P < 0.05). The mean posttest menopausal symptom score (t = −8.99, P = 0.01**) was significantly low and the mean health-promoting behavior score (t = 8.7, P = 0.01**) was significantly high in the experimental group. Conclusion: Based on the finding of the study, it can be concluded that Lifestyle modification program was significantly effective in reducing menopausal symptoms and improving health-promoting behaviors among women.